Coalition Formation in Simple Games: The Semistrict Core - Dinko Dimitrov; Claus-Jochen Haake (Fondazione Eni Enrico Mattei (FEEM), 2006)
We consider the class of proper monotonic simple games and study coalition formation when an exogenous share vector and a solution concept are combined to guide the distribution of coalitional worth. Using a multiplicative composite solution, we induce players' preferences over coalitions in a hedonic game, and present conditions under which the semistrict core of the game is nonempty.
Keywords: D72; C71; 330; Coalition Formation; Paradox of Smaller Coalitions; Semistrict Core; Simple Games; Winning Coalitions; Koalition; Spieltheorie